2021
DOI: 10.3390/app11167205
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Pyrolysis of Lignin Model Compounds (Pyrocatechol, Guaiacol, Vanillic and Ferulic Acids) over Nanoceria Catalyst for Biomass Conversion

Abstract: Understanding the mechanisms of thermal transformations of model lignin compounds (MLC) over nanoscale catalysts is important for improving the technologic processes occurring in the pyrolytic conversion of lignocellulose biomass into biofuels and value-added chemicals. Herein, we investigate catalytic pyrolysis of MLC (pyrocatechol (P), guaiacol (G), ferulic (FA), and vanillic acids (VA)) over nanoceria using FT-IR spectroscopy, temperature-programmed desorption mass spectrometry (TPD MS), and thermogravimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 81 publications
(177 reference statements)
2
18
0
Order By: Relevance
“…In the study put forth by [35], the pCmA absorption in this region was attributed to β(CH) C=C . Although it was known that for phenolic acids (ferulic, vanilla, and caffeic), β(OH) bands could also be found in this part of the spectrum [16,[36][37][38]40]. The detected changes may have been due to the formation of carboxylate complexes on the oxide surface.…”
Section: Fourier Transform-infrared (Ft-ir) Spectroscopymentioning
confidence: 95%
See 4 more Smart Citations
“…In the study put forth by [35], the pCmA absorption in this region was attributed to β(CH) C=C . Although it was known that for phenolic acids (ferulic, vanilla, and caffeic), β(OH) bands could also be found in this part of the spectrum [16,[36][37][38]40]. The detected changes may have been due to the formation of carboxylate complexes on the oxide surface.…”
Section: Fourier Transform-infrared (Ft-ir) Spectroscopymentioning
confidence: 95%
“…Analysis of our previous data of catalytic pyrolysis of cinnamic acids [16,40] and the results of deconvolution of the TPD curve for ion with m/z 120 (4-vinylphenol) suggested that following peaks II-IV (Figure 6) were due to decarboxylation of different types of surface complexes (Scheme 2). Earlier, we found that coumaric acid is a thermally unstable compound and decomposes via heating.…”
Section: Pyrolysis Of P-coumaric Acid Over Nanoceriamentioning
confidence: 99%
See 3 more Smart Citations